Open strategic autonomy in EU trade policy assessing the turn to stronger enforcement and more robust interest representation - Weiss, Wolfgang; Furculita, Cornelia (Cambridge studies in European law and policy, 2024)
This book analyses whether the recent reorientation of EU trade policy towards stronger enforcement and more robust representation of interests, resulting in a series of new or amended legislative tools, is in conformity with the EU's international commitments, particularly WTO, FTA, environmental, and general international law, and with its multilateralist stance and underlying constitutional obligations. The analysis is also set against the consequences that would flow from within the EU legal order, providing readers with a comprehensive view of the external and internal constraints on trade policy that the EU should respect, as well as the leeway it enjoys. In case of potential tensions, it submits changes that would better balance the EU's new ambitions and international obligations. Furthermore, the book looks beyond the possible legal repercussions to consider the broader political implications of these instruments on the credibility of the EU's commitment to multilateralism and international law